Retta language revitalization learning materials in Alor Regency - Budiono, Satwiko; Noviani, Evi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
Currently there are various learning materials that are able to motivate younger generations in learning local and indigenous languages. One example is the creation of songs in Retta language revitalization program in Alor Regency. In this regard, this study seeks to explain the process of revitalizing the Retta language and reviewing the effectiveness of revitalizing the Retta language through local language songs as learning materials. This is important because language and culture transmission through songs is a novelty in a language revitalization program. The research method uses a community—based language revitalization model and a descriptive qualitative approach with observational method from the analysis of Retta language songs in the language revitalization program. As a result, the Retta language revitalization in the South Ternate Village using local language songs is effective in increasing the interest of young speakers in the local language. This is based on the impact felt by the language revitalization participants as young speakers and Retta speakers in general. Besides that, the Retta language revitalization program was also able to raise public and local government awareness with evidence of the signing of a memorandum of understanding to preserve the Retta language in the future. Thus, the Retta language revitalization program using local language songs can continue to be developed by the local government.